Cohabiting commerce in a transport hub: peoples as infrastructure in Lagos, Nigeria (2019)
Based on a case study of Iyana Ipaja, one of the largest transport hubs with a spacious motor park and the most vibrant markets in North Lagos, we elaborate on the nuances of interactions between commercial actors and various forms of infrastructure in the spatial and temporal senses. In terms of materiality and mobility of their businesses, commercial actors are categorised into three types, shopkeepers, stallholders and hawkers. They have extensive interactions with the objects with which they are attached (shops, stalls and goods), the physical infrastructures (vehicles, roads, bus stations and motor parks), and ‘people as infrastructure’ – a term coined by Simone – including drivers, passengers, passers-by and government agencies. We suggest that a modification to the concept of ‘peoples as infrastructure’ should help to articulate interactions among differently positioned actors. We argue that the localities and mobilities of commercial practices manifest spatial conviviality among peoples as infrastructure. The temporality of their commercial practices is embedded in the urban rhythm of Lagos and remediates the flows of people and vehicles through the spaces of Iyana Ipaja. The focus of commercial actors provides a new perspective to rethink grassroots spatial politics of motor parks in Nigeria. Moreover, this case study critically engages the theory of relationality of ‘people as infrastructure’ in urban Africa.